1998
DOI: 10.1136/adc.79.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted organisms in sexually abused children

Abstract: Conclusions-There is a low prevalence of definitely sexually transmitted organisms in children who might have been abused. Other organisms possibly associated with sexual activity can be identified in this population. Screening for infection should be mandatory in presumed sexually abused girls with vaginal discharge and ideally should be undertaken in all children attending for evaluation of sexual abuse. (Arch Dis Child 1998;79:356-358)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…The prevalence of HSV, mostly HSV-2, infection in these studies was low, Ͻ5% (20,26,38,44,47,63,65). In a recent multicenter study reported by Girardet et al, only 12 girls were found to have genital ulcers, 5 of whom were culture positive for HSV-2 (26).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of HSV, mostly HSV-2, infection in these studies was low, Ͻ5% (20,26,38,44,47,63,65). In a recent multicenter study reported by Girardet et al, only 12 girls were found to have genital ulcers, 5 of whom were culture positive for HSV-2 (26).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Most published studies of STIs in sexually abused children that tested for T. vaginalis were limited to girls presenting with vaginal discharge (20,26,38,44,47,63,65). However, an identification of T. vaginalis appears to be strongly associated with sexual activity.…”
Section: Trichomonas Vaginalismentioning
confidence: 99%
See 1 more Smart Citation
“… a paediatric assessment behavioural indicators tests for other STD in the child and carers typing of warts is expensive and may be misleading as non-genital wart types may be sexually transmitted—for example, digital and genital wart types transmitted in utero a social worker with or without police investigation follow up appointments for adolescents are recommended, joint clinics with genitourinary physicians are ideal5 follow up of prepubescent children is more difficult and currently we refer back to the general practitioner for assessment, possibly at the first family planning clinic locally, treatment of AGW is surgical. …”
mentioning
confidence: 99%
“…follow up appointments for adolescents are recommended, joint clinics with genitourinary physicians are ideal5 …”
mentioning
confidence: 99%